MENINGKATAN HASIL BELAJAR LARI CEPAT MELALUI PERMAINAN SIAPA CEPAT DIA DAPAT SISWA SD (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study was to determine the improvement of learning outcomes quick run through approachpermaianan Quick Who He used DapatAdapun subject is class V Elementary School District 02 SambirotoKajen District of Pekalongan in the second semester of academic year 2013/2014. Instruments used incollecting data obtained from the test results shown student performance during the implementation of the test.Data analysis was done descriptively comparative aimed to compare the conditions before and after thelearning corrective action is held. From the results of research conducted, an increase in student learningoutcomes from initial conditions to cycle 1 and cycle 2, both of the progressive increase in the average value oflearning to run faster or completeness value of learning outcomes. The average value kondidi early (72.39), theaverage cycle 1 (75.26) and the average cycle 2 (77.94), so that an increase from baseline to 2 cycles of (5.5).Increased ability to run fast motion on learning can be seen from the KKM (75) or completed at 41.94%, afterthe action on the first cycle of students who pass the value of learning as much as 18 of the 31 students (58.06%)and in cycle 2 has a value above KKM as many as 25 out of 31 students overall or completed by (80.65%).